2004
DOI: 10.1128/jvi.78.10.5311-5323.2004
|View full text |Cite
|
Sign up to set email alerts
|

Nef Binds p6* in GagPol during Replication of Human Immunodeficiency Virus Type 1

Abstract: Human immunodeficiency virus type 1 (HIV-1), the causative agent of AIDS, encodes 16 distinct proteins that are expressed differentially during the viral replicative cycle. Initially, the early regulatory proteins Tat and Rev and the socalled negative effector (Nef) are translated from multiply spliced mRNA species. During late phases, singly spliced or unspliced transcripts direct the expression of viral accessory proteins (viral proteins R and U [Vpr and Vpu] and viral infectivity factor [Vif]), as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 52 publications
1
28
0
1
Order By: Relevance
“…In support of this idea, a recent study reported that Nef affected the membrane trafficking and proteolytic processing of HIV Env (138). Also, it has been reported that Nef binds to Gag-Pol via the C-terminal flexible loop (34). Finally, Nef was recently shown to increase the localization of viral glycoproteins on endosomal membranes in producer cells and to also increase the incorporation of these molecules into viral particles (135).…”
Section: Nef-induced Alterations In Protein Transport and Hiv Infectimentioning
confidence: 57%
“…In support of this idea, a recent study reported that Nef affected the membrane trafficking and proteolytic processing of HIV Env (138). Also, it has been reported that Nef binds to Gag-Pol via the C-terminal flexible loop (34). Finally, Nef was recently shown to increase the localization of viral glycoproteins on endosomal membranes in producer cells and to also increase the incorporation of these molecules into viral particles (135).…”
Section: Nef-induced Alterations In Protein Transport and Hiv Infectimentioning
confidence: 57%
“…In this regard, p6* has also been proposed to be a possible binding partner of the viral Nef protein, the major pathogenicity factor during HIV infection (9). However, the target site within p6* for Nef interaction has not been mapped so far.…”
mentioning
confidence: 99%
“…The 160-kDa Gag-Pol protein contains the polencoded transframe (TF) protein and the essential viral enzymes protease (PR), reverse transcriptase (RT), and integrase (IN), which are efficiently packaged into the viral particle. Through an interaction with the C terminus of Nef, the TF protein of the Gag-Pol precursor in turn packages Nef into the virion (8).…”
mentioning
confidence: 99%